VIETNAM - FRANCE STRATEGIC PARTNERSHIP: SOME ISSUES IN ECONOMIC RELATIONS (2013-2023) - Ung Hoang Anh*, Do Thi Thanh Loan (Tạp chí Khoa học)
On April 12th, 1973, the Democratic Republic of Vietnam (renamed the Socialist Republic of Vietnam in July 1976) and the French Republic officially established diplomatic relations. Over the past 50 years, the bilateral relationship between Vietnam and France has experienced various ups and downs but has also achieved significant milestones. This research focuses on presenting the economic relationship between Vietnam and France for over 10 years, from establishing the Strategic Partnership in 2013 to 2023. Furthermore, we identify potential advantages and challenges in the economic cooperation between Vietnam and France in the upcoming period to provide recommendations for further deepening the economic cooperation process between the two countries within the framework of the current Comprehensive Strategic Partnership.